Solutions for vehicular communications: a review - Soares, V.N.G.J. (2011)
Vehicular networks experience a number of unique challenges due to the high mobility of vehicles and highly dynamic network topology, short contact durations, disruption intermittent connectivity, significant loss rates, node density, and frequent network fragmentation. All these issues have a profound impact on routing strategies in these networks. This paper gives an insight about available solutions on related literature for vehicular communications. It overviews and compares the most relevant approaches for data communication in these networks, discussing their influence on routing strategies. It intends to stimulate research and contribute to further advances in this rapidly evolving area where many key open issues that still remain to be addressed are identified.